Pengaruh Fee Based Income Dan Giro Wajib Minimum Terhadap Profitabilitas Bank Syariah Indonesia (BSI) - Riska Adwiyah Hasibuan; Annio Indah Lestari Nasution; Kharina Tambunan (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This research was conducted to determine the effect of Fee Based Income and Minimum Statutory Reserves on the Profitability of PT. Indonesian Sharia Bank. The population used in this research is the financial statements of PT. Indonesian Sharia Bank. Meanwhile, samples were taken from the monthly financial reports of Bank Syariah Indonesia for 2020 - 2022 using purpusive sampling techniques. The results of this research show that the value of Tcount > Ttable or 5.865 > 2.03452 and the significant value of the Fee Based Income variable (X1) is 0.000 < 0.050, stating that partially the Fee Based Income variable has a significant effect on Profitability. The value of Tcount > Ttable or 7.901 > 2.03452 and the significant value of the Minimum Statutory Reserve variable (X2) is 0.000 < 0.050. Minimum Statutory Reserves have a significant effect on Profitability. Fcount > Ftable or 51,929 > 2.90 with a probability value of 0.000 < 0.050, it can be concluded that H0 is rejected and Ha is accepted, meaning that Fee Based Income and Minimum Statutory Reserves simultaneously influence Profitability.